Human resources well-being in innovative start-ups: Insights from a systematic review of the literature - Salvatore Ammirato; Alberto Michele Felicetti; Ciro Troise; Gabriele Santoro; Zoltan Rozsa (Journal of Innovation & Knowledge (JIK), 2024)
This study aims to unify the fragmented knowledge on human resource (HR) well-being in innovative start-ups, a critical factor in their success. Through a systematic literature review, we analysed 42 peer-reviewed articles using MySLR software to identify key themes and dimensions in this area. Our findings suggest that HR well-being in start-ups can be understood as a higher-order construct, encompassing three main dimensions: job satisfaction, psychological well-being, and work-life balance, including gender-related considerations. The study's implications are significant for academics and practitioners; as such, the proposed framework serves as a reference model for future research and a practical guide for start-up managers to improve employee well-being. The originality of this study lies in its comprehensive approach to synthesising existing research on HR well-being in start-ups, providing a unified framework that clarifies previously unclear and fragmented findings in the literature.
Keywords: O15; O30; 650; Start-up; Well-being: Human resources; Innovation